2020
DOI: 10.1186/s12992-020-00601-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of depression and its correlative factors among female adolescents in China during the coronavirus disease 2019 outbreak

Abstract: Background The outbreak of 2019 coronavirus disease (COVID-19) could increase the risk of depression. However, epidemiological data on outbreak-associated depressive morbidity of female adolescents are not available. This study determines the incidence and correlates of depression among female adolescents aged 11–18 years during the COVID-19 outbreak in mainland China. Methods A large cross-sectional sample, nationwide online survey was conducted during the COVID-19 out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
101
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(109 citation statements)
references
References 20 publications
7
101
1
Order By: Relevance
“…The high school students reported increased feelings of "loneliness" and "boredom", as well as heightened levels of 'anxiety about the future effects of the ongoing COVID-19 pandemic' similar to what have been observed in previous studies (2,(4)(5)(6)(7)(8)(9)(10)(26)(27)(28)(29)(30). They also reported lower levels of positive affects, and higher levels of negative counterparts, compared to the previous studies investigating the adolescents prior to the pandemic (21)(22)(23)(24)(25).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The high school students reported increased feelings of "loneliness" and "boredom", as well as heightened levels of 'anxiety about the future effects of the ongoing COVID-19 pandemic' similar to what have been observed in previous studies (2,(4)(5)(6)(7)(8)(9)(10)(26)(27)(28)(29)(30). They also reported lower levels of positive affects, and higher levels of negative counterparts, compared to the previous studies investigating the adolescents prior to the pandemic (21)(22)(23)(24)(25).…”
Section: Discussionsupporting
confidence: 74%
“…We hypothesized that the impact would be greater among economically disadvantaged adolescents. While current data indicate that adolescents' psychological status and motivation are negatively affected by the pandemic and online education (2)(3)(4)(5)(6)(7)(8)(9)(10), to the best of our knowledge, data on cross-cultural differences and whether there are any differences among public versus private school students are largely missing. Therefore, in this study we aimed to analyze the effects of both the pandemic and distance learning on social and psychological status of high school students in Turkey, with special emphasis to see whether attending public or private school systems had an effect.…”
Section: Introductionmentioning
confidence: 92%
“…Eight were from China, 45,50,68,70,72-74,77 7 from other low and middle-income countries (LMIC; Turkey, 58,79 Pakistan, 25 India, 28,65 Brazil, 55 Bangladesh 76 ) and 13 from Italy, 23,26,27,32,35,38,49,56,78,81,84-86 21 from the UK, 22,29-31,37,39-42,44,47,48,54,60,62-64,69,87,89,90 12 from the USA, 24,43,46,51,57,59,66,67,71,75,92,94 and 1 study each from Ireland, 88 France, 91 Germany, 93 Greece, 80 Spain, 61 Finland, 34 Slovenia, 33 Israel, 82,83 Australia, 52 Canada 53 and Japan. 36…”
Section: Resultsmentioning
confidence: 99%
“…While Spain established a stringent and wide-spread lockdown -lasting up to six weeks-to control the spread of the virus (see [2] and Figure1), many have raised concern regarding the putative consequences for mental health, particularly in vulnerable groups such as children and adolescents [1,4]. Early reports have revealed huge distress, anxiety and depression in some of these groups [5], but little is known about the psychological impact speci cally for youths [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, in the context of COVID-19, social isolation might worsen anxiety, depression and stress [4]. The rst COVID-19 studies in China found increased anxiety, stress, and depression symptoms in adolescent females, with a 39.5% of this population meeting criteria for clinical depression [7,8]. In another sample of children and adolescents, depression symptoms were signi cant on 22% of respondents, with greater risk associated with female sex, emotion-focused coping style and being an urban resident [23].…”
Section: Introductionmentioning
confidence: 99%